Effects of small doses of cytochalasins on fibroblasts: preferential changes of active edges and focal contacts. - Domnina, L V (1982)
The effects of low doses of cytochalasin B (2 micrograms/ml) and cytochalasin D (0.2 microgram/ml) on the spreading of normal mouse fibroblasts in culture were investigated to find out which components of cell-substrate interactions are most sensitive to alterations of the state of actin cytoskeleton. Cytochalasin B disorganized the cortical layer of actin microfilaments and caused partial or complete disappearance of microfilament bundles; focal contacts with the substrate seen by interference-reflection microscopy also disappeared. Diffuse close contacts were apparently insensitive to cytochalasin B. Low doses of cytochalasin B did not inhibit the outgrowth and maintenance of lamellas at the cell periphery. However, in contrast to controls, these lamellas had no distal zones with convex outer edges and ruffles at the upper surfaces. The disappearance of these ruffling active edges was accompanied by loss of the ability to clear the surface of the lamellas from the concanavalin A receptors crosslinked by the corresponding ligand. The effects of cytochalasin D were similar to those of cytochalasin B. Thus, ruffling active edges and focal contacts can be regarded as specialized parts of lamellas with increased sensitivity to cytochalasins; the presence of ruffling active edges is essential for the initiation of centripetal movement of the patches of crosslinked surface receptors.